Analyzing Civics Education Teachers' Difficulties in Applying Merdeka Curriculum at SMPN 9 Kota Bima - Fahmi, Muhammad Rizal; Muchtarom, Moh.; Winarno, Winarno (Indonesian Journal of Multidisciplinary Science, 2023)
The research objective is to analyze the difficulties faced by Pancasila and Citizenship Education teachers in implementing the role of the Merdeka Curriculum in SMPN 9 Kota Bima. The research method used is qualitative research. The data collection method used in this research is observation, interviews, and documentation. The types of interviews conducted are structured and unstructured interviews. Meanwhile, the data collection technique used for the research subjects is purposive sampling. The research findings indicate that (1) there is a need for development in students literacy skills and a need for updating the reference materials used for learning, such as providing more update books and other learning materials; (2) The issue of students background and environmental influences that make it more difficult to apply conservative roles; (3) Some teachers are not yet proficient in using technology as a learning tool, and there are some students who do not have a handphone as a supporting tool for the learning process, thus making the learning process less effective; (4) Pancasila and Citizenship Education teachers have difficulty controlling students' use of technology during the learning process. Next mstarting from the reduced norms of decency and decency due to the influence of social media content. and dsstudents are not focused during the learning process because they are busy using other applications.